Analisis SWOT terhadap Implementasi Fintech Syariah - Mutakin (Jurnal Riset Ekonomi Syariah, 2025)
Abstract. This study aims to analyze the strategic position of Islamic fintech in Indonesia using a SWOT approach and to evaluate its contribution to financial inclusion and the enhancement of an economy based on Islamic values. The research employs a qualitative descriptive method, collecting data through semi-structured interviews with regulators, fintech practitioners, academics, and consumers, as well as a literature review of official documents, industry reports, and scholarly publications. The findings indicate that Islamic fintech possesses strengths in its strong Shariah foundation, large Muslim market potential, and institutional support, yet faces weaknesses such as low financial literacy, limited multidisciplinary human resources, and suboptimal supervision. Opportunities arise from digitalization trends, integration with the halal economy, and regulatory support, while threats stem from competition with conventional fintech and cybersecurity risks. These findings provide practical contributions for regulators and industry stakeholders to formulate sustainable Islamic fintech development strategies and offer theoretical contributions to the study of Islamic finance in the digital era. Abstrak. Penelitian ini bertujuan untuk menganalisis posisi strategis fintech syariah di Indonesia dengan pendekatan SWOT, serta mengevaluasi kontribusinya terhadap inklusi keuangan dan penguatan ekonomi berbasis nilai Islam. Penelitian menggunakan metode kualitatif deskriptif dengan pengumpulan data melalui wawancara semi-terstruktur kepada regulator, praktisi fintech, akademisi, dan konsumen, serta studi pustaka dari dokumen resmi, laporan industri, dan publikasi ilmiah. Hasil penelitian menunjukkan bahwa fintech syariah memiliki kekuatan pada fondasi syariah yang kuat, potensi pasar Muslim yang besar, dan dukungan kelembagaan, namun menghadapi kelemahan berupa rendahnya literasi keuangan, keterbatasan SDM multidisiplin, dan pengawasan yang belum optimal. Peluang muncul dari tren digitalisasi, integrasi ekonomi halal, dan dukungan regulasi, sedangkan ancaman berasal dari persaingan fintech konvensional dan risiko keamanan siber. Temuan ini memberikan kontribusi praktis bagi regulator dan pelaku industri untuk merumuskan strategi pengembangan fintech syariah yang berkelanjutan serta kontribusi teoretis dalam studi keuangan Islam berbasis teknologi.